La sobreprotección familiar y su incidencia en el rendimiento escolar de los niños 5-6 años de edad de la escuela de educación básica “IV Centenario” en el periodo lectivo 2018 - Gaona Gonzaga, Dayanna Patricia (2019)
The present research work is framed in the study titled, THE FAMILY OVERPROTECTION AND ITS INCIDENCE IN THE SCHOOL PERFORMANCE OF CHILDREN OF 5-6 YEARS OF AGE OF THE BASIC EDUCATION SCHOOL "IV CENTENARY" IN THE 2018 LECTIVE PERIOD. Purpose of identifying the characteristics of overprotection manifested by the parents of first-year children, that is why within the objectives set out in the research are as a general objective: Contribute to the modification of overprotective behaviors that children show First year of the School of Basic Education "IV Centenario" for the 2018 elective period. The research was of a descriptive-scientific nature, with a quantitative-qualitative approach and participatory action, using scientific, inductive and descriptive methods. The instrument used for the Investigation was the observation guide of (Carlos, 2014), adapted by the researcher and the Survey Technique prepared by the same author and adapted by the researcher. The results allow to conclude that the children have characteristics of overprotection for which they also obtain grades that are below or in the general average in their school performance. Based on this, it was recommended to promote opportunities to meet with parents so that they assume new attitudes to the particularities of overprotection of children